Calcipenic states in pediatrics and neuropediatrics: approaches to its prevention and treatment - V. M. Studenikin (Лечащий Врач, 2022)
The paper is dedicated to calcipenic states in pediatric patients and contemporary considerations on the approaches to its prevention and treatment. Some basic definitions and terms related to the problem of calcipenic conditions are included. Main functions of Ca in human organism are regarded, the mechanisms for Ca regulation are mentioned as well along with some most important manifestations of this macronutrient’s deficiency, pertaining to endocrine, cardiovascular and central nervous systems (including cognitive decline) plus Ca-associated symptoms from bone tissue and skin. A number of hormones functioning as main regulators for this extremely important macroelement’s metabolism in human organism are alluded (parathyroid hormone, calcitonin, secosteroid calcitriol, thyroliberine, thyroxine, triiodothyronine, somatotropic hormone and insulin). The most important causes for calcipenia in pediatric patients of various age groups are described. The similarities between etiological factors for calcipenia formation and bone fragility states (osteopathies) such as osteoporosis and osteomalacia are described. The approaches to correction (via prevention and treatment) of calcipenic states using available Ca sources are considered. Special emphasis is placed on the potential role and benefits of domestic (Russian-manufactured) biologically active dietary supplement – liquid Calcium, which includes a combination of Ca lactate / phosphate, vitamin D3 (cholecalciferol) and vitamin K1 (phytomenadione / phylloquinone). In conclusion, the predictive role of Ca deficiency for cardiovascular and neurological complications in patients with COVID-19 infection is noted. Data of Russian and foreign researchers involved in the problem of Ca deficiency in various clinical situations is quoted.